Prospective assessment of serum periostin as a biomarker for diagnosis and monitoring of eosinophilic oesophagitis. Issue 2 (18th May 2016) - Dellon, E. S.; Higgins, L. L.; Beitia, R.; Rusin, S.; Woosley, J. T.; Veerappan, R.; Selitsky, S. R.; Parker, J. S.; Genta, R. M.; Lash, R. H.; Aranda, R.; Peach, R. J.; et al.
Summary: Background: Periostin is highly expressed in eosinophilic oesophagitis (EoE), but has not been extensively studied as a non‐invasive biomarker. Aim: To assess whether serum periostin distinguished EoE from controls at baseline, had utility for monitoring treatment response, or was associated with IL‐13 levels. Methods: This was a sub‐analysis of a prospective cohort study of adults undergoing out‐patient upper endoscopy. Incident cases of EoE were diagnosed per consensus guidelines. Controls were subjects with either GERD or dysphagia without EoE. EoE patients were treated with swallowed/topical steroids and had repeat endoscopy/biopsy. Serum periostin levels for cases and controls were compared at baseline, and pre/post‐treatment levels were compared for cases. Serum IL‐13 and tissue expression of periostin were also assessed. Results: A total of 61 incident EoE cases and 87 controls were analysed. Despite a marked increase in tissue periostin expression in cases, the median baseline serum periostin level was only slightly higher in cases than controls (22.1 ng/mL vs. 20.7; P = 0.04); there was no change in post‐treatment levels. There was also no difference in serum periostin for cases by histologic response or atopic status. There was a strong trend towards higher serum IL‐13 levels in cases in the highest periostin quartile (57.1 pg/mL vs. 2.6; P = 0.07). Conclusions: Serum periostin levels were similar in cases and controls, and there were no changes post‐treatment. Given elevated IL‐13 levels in the EoE patients with the highest periostin levels, future studies could explore periostin as a biomarker in EoE, perhaps in the setting of anti‐IL‐13 therapy.